Expect the unexpected - Implications for next phase of COVID-19 response - Sarah Clifford; Muge Cevik; Robyn Campbell; Dàire O'Shea; Rebecca Sutherland (Elsevier, 2021)
Summary: A case report of a 66 year old male patient with COVID 19 who presented late in the clinical course and subsequently developed respiratory failure requiring intubation, after initially experiencing diarrhoea.